Evaluasi Strategi Kebijakan tentang Bullying dan Dampaknya terhadap Kesehatan Mental Remaja di SMA Negeri 1 Plus Matauli Pandan - Rahmiati Rizkiyah Siregar; Asriwati Asriwati; Yuniati Yuniati (Jurnal Kesehatan Amanah, 2025)
Bullying is a global problem that affects adolescents' mental health as well as the quality of education. This study aims to evaluate the anti-bullying policy at SMA Negeri 1 Plus Matauli Pandan and identify its impact on the psychological well-being of students. The research method uses a qualitative approach with a phenomenological design. A total of nine informants were selected through purposive sampling, consisting of key, main, supportive, and triangulated informants. Data was obtained through in-depth interviews and document review, then analyzed using the CIPP (Context, Input, Process, Product) evaluation model. The findings of the study show that anti-bullying policies are rooted in the vision, mission, and Student Honor Code of Conduct that rejects all forms of bullying. In terms of input, the involvement of BK teachers, homeroom teachers, students, and parents plays an important role, although the limited number of counselors is still an obstacle. The implementation process is carried out through socialization, routine supervision, and counseling with an emphasis on prevention and rehabilitation aspects. Product evaluations showed a significant decrease in cases of physical bullying, although verbal behavior was still found. This policy has a positive impact by increasing students' sense of security, confidence, and learning comfort, while encouraging changes in the attitude of perpetrators. Based on these results, the study recommends strengthening anti-bullying literacy, consistency in the implementation of sanctions, and developing broader psychosocial services. These efforts are needed to ensure the sustainability of the policy while supporting adolescent mental health.